Molecular characteristics of BRCA1/2 and PALB2 mutations in pancreatic ductal adenocarcinoma. Issue 6 (23rd November 2020) - Seeber, Andreas; Zimmer, Kai; Kocher, Florian; Puccini, Alberto; Xiu, Joanne; Nabhan, Chadi; Elliott, Andrew; Goldberg, Richard M; Grothey, Axel; Shields, Anthony F; Battaglin, Francesca; El-Deiry, Wafik S; et al.
Abstract : Introduction: Poly-(ADP)-ribose polymerase (PARP) inhibitors are successfully used for treatment of BRCA- mutated (mut) breast cancers and are under extensive evaluation for BRCA- and PALB2- mutated pancreatic ductal adenocarcinoma (PDAC). However, the optimal treatment regimen for BRCA/PALB2 -mutated PDCA has yet to be established. Moreover, limited data are available on the association of BRCA/PALB2 gene alterations with other comutations and immunological biomarkers. Material and methods: Tumour samples of 2818 patients with PDAC were analysed for BRCA 1/2 PALB2 mutations and other genes by next-generation sequencing (NGS) (MiSeq on 47 genes, NextSeq on 592 genes). TMB was calculated based on somatic non-synonymous missense mutations. MSI-H/dMMR was evaluated by NGS, and PD-L1 expression was determined using immunohistochemistry. Results: In 4.2% (n=124) of all PDAC samples BRCA mutations have been detected. BRCA2 mutations were more commonly observed than BRCA1 mutations (3.1%(n=89) vs 1.1% [n=35], p<0.0001). BRCA2 mutation was associated with an older age (64 vs 61 years for wild-type (wt), p=0.002) and PALB2 mutation was observed more frequently in female than in male patients. BRCA and PALB2 mutations were associated with MSI-H/dMMR compared with wt ( BRCA : 4.8% vs 1.2%, p=0.002; PALB2 : 6.7% vs 1.3 %, p=0.18), PD-L1 expression of >1.0% ( BRCA : 21.8% vs wt 11.2%, p<0.001, PALB2 : 0.0% vs 12.4 %, p=0.38) and high TMB ( BRCA : mean 8.7 vs 6.5 mut/MB, p<0.001; PALB2 : 10.6 mut/Mb vs 6.6 mut/Mb, p=0.0007). Also, PD-L1 expression and TMB differed between BRCA and PALB2 mutation and wt samples in MSS tumours (p<0.05). BRCA -mutated and PALB2 -mutated PDACs were characterised by a different mutational profile than was observed in wt tumours. Conclusions: BRCA and PALB2 mutations were found in a significant subgroup of PDACs. These mutations were associated with a distinct molecular profile potentially predictive for response to immune-checkpoint inhibitor therapy. Therefore, these data provide a rationale to evaluate PARP inhibitors in combination with immune-checkpoint inhibitors in patients with BRCA/PALB2 -mutated PDAC.